2011
DOI: 10.1021/tx200025y
|View full text |Cite
|
Sign up to set email alerts
|

GSH-Mediated S-Transarylation of a Quinone Glyceraldehyde-3-Phosphate Dehydrogenase Conjugate

Abstract: Many cellular proteins with reactive thiols form covalent bonds with electrophiles, thereby modifying their structures and activities. Here, we describe the recovery of a glycolytic protein, glyceraldehyde-3-phosphate dehydrogenase (GAPDH), from such an electrophilic attack by 1,2-napthoquinone (1,2-NQ). GAPDH readily formed a covalent bond with 1,2-NQ through Cys152 at a low concentration (0.2 μM) in a cell-free system, but when human epithelial A549 cells were exposed to this quinone at 20 μM, only minimal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 39 publications
1
34
0
Order By: Relevance
“…1) (Kumagai et al, 2012;Miura et al, 2011a). For example, sensor proteins containing reactive nucleophiles undergo arylation by 1,2-NQ, thereby disrupting their function (Endo et al, 2011(Endo et al, , 2007Iwamoto et al, 2007;Miura et al, 2011aMiura et al, , 2011bSumi et al, 2010). In a previous study, we found that several unidentified proteins expressed by human pulmonary epithelial A549 cells are modified after exposure to 1,2-NQ (Miura et al, 2011b).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…1) (Kumagai et al, 2012;Miura et al, 2011a). For example, sensor proteins containing reactive nucleophiles undergo arylation by 1,2-NQ, thereby disrupting their function (Endo et al, 2011(Endo et al, , 2007Iwamoto et al, 2007;Miura et al, 2011aMiura et al, , 2011bSumi et al, 2010). In a previous study, we found that several unidentified proteins expressed by human pulmonary epithelial A549 cells are modified after exposure to 1,2-NQ (Miura et al, 2011b).…”
Section: Introductionmentioning
confidence: 94%
“…SDS-PAGE and subsequent immunoblot analysis were performed as reported previously (Miura et al, 2011a). The protein concentrations were determined using the Bio-Rad Protein assay kit (Bio-Rad, Richmond, CA, USA) or the bicinchoninic acid (BCA) protein assay reagent (Pierce Biotechnology Inc., Rockford, IL, USA), incorporating bovine serum albumin as a standard.…”
Section: Western Blottingmentioning
confidence: 99%
See 1 more Smart Citation
“…Using anti-1,2-NQ, it has been demonstrated that protein tyrosine phosphatase 1B (PTP1B) (Iwamoto et al, 2007), cAMP response element-binding protein (Endo et al, 2007), inhibitory κB kinase β (Sumi et al, 2010), Kelch-like ECH-associated protein 1 (Keap1) (Miura et al, 2011c), glyceraldehyde-3-phosphate dehydrogenase (Miura et al, 2011a(Miura et al, , 2011b, peroxiredoxin 6 (Takayama et al, 2011) and thioredoxin1 are molecular targets of 1,2-NQ for covalent modification. More importantly, it has been shown that activations of epidermal growth factor receptor and NF-E2-related factor 2 (Nrf2) are attributable to S-arylation of PTP1B through Cys121 and of Keap1 through Cys151 by 1,2-NQ, respectively (Iwamoto et al, 2007;Kobayashi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…NRF2 binds to a cognate DNA regulatory element termed the antioxidant response element and up-regulates its target genes. Of interest, 1,2-NQ also activates NRF2 through covalent modification of Keap1 (10). Collectively, it seems likely that there are different adaptive responses against environmental electrophiles, such as 1,2-NQ, via activating signal transduction pathways.…”
mentioning
confidence: 99%